miR-600 promotes ovarian cancer cells stemness, proliferation and metastasis via targeting KLF9 - Lili Shan; Pingping Song; Yangyang Zhao; Na An; Yanqiu Xia; Yue Qi; Hongyan Zhao; Jing Ge (BMC, 2022)
Abstract Previous studies have revealed that miRNAs participate in the pathogenesis of ovarian cancer; however, whether miR-600 is also involved remains unclear. In this study, we aimed to investigated the role of miR-600 in ovarian cancer progression. Here, miR-600 expression was significantly upregulated in ovarian cancer tissues and stem cells. Functional studies showed that miR-600 promoted ovarian cancer cell stemness, proliferation and metastasis. Mechanistic studies revealed that Kruppel like factor 9 (KLF9) was indicated as the target of miR-600. The luciferase reporter assay suggested that miR-600 directly bound to the 3'-untranslated region of KLF9. Additionally, miR-600 expression was negatively associated with KLF9 expression in human ovarian cancer tissues. Si-KLF9 partially abolished the discrepancy of self-renewal, growth and metastasis capacity between miR-600 knockdown ovarian cancer cells and control cells. In conclusion, our results suggest that miR-600 promotes ovarian cancer cell stemness, proliferation and metastasis via directly downregulating KLF9, and impairing miR-600 levels may be a new treatment strategy for ovarian cancer in the future.